What Was Parliamentary Reporting? A Study of Aims and Results in the London Daily Newspapers, 1780–96. (2nd June 2020) - Harris, Ian
Abstract: The nature of these newspaper reports – that is, the character of their principal content – has never been studied, despite its obvious importance and, as we shall see, its marked differences from our Hansard. This article relates their nature to a vital feature of parliamentary leadership, the ability to lead the argument in debate. The practical reasoning in parliamentary deliberation and justification, especially what speakers contributed towards the outcome or 'the sense of the debate', predominated in these reports. This implied a need for reporters to concentrate on the 'substance' of speeches and their bearing on the motion. One result was that speeches which were judged to define or develop arguments pro and con were treated at length, the defining speeches most extensively and others in proportion to what they added. Conversely, speeches which reiterated known positions or which were irrelevant to the arguments in hand were omitted or downplayed, even if they were important in some other way, while whole debates which added little to ongoing discussion could be treated quite briefly. But if being a front bencher did not guarantee coverage, being a back bencher was no bar: the criterion was the importance of a speaker's contribution, while the manner of coverage accented what was contributed. The reporters' concerns emphasized debates that promised significant change in matters of national importance, but gave relatively little attention to recurrent or localised business as such. Their writing – they were known as debate writers or news‐writers – was interpretation answering to evaluative and selective criteria rather than a record in a simple sense. Their work is not to be understood in the same terms as a modern Hansard, and in particular not as a defective Hansard, but rather is such that it requires further work on a wide range of new research questions if it is to be understood to best effect, a requirement which suggests a need to study it critically before using it as source material.